Biofilm removal technique using sands as a research tool for accessing microbial attachment on surface - Nathanon Trachoo (Songklanakarin Journal of Science and Technology (SJST), 2004)
Biofilms have profound impacts on improved survival of the constituent microorganisms in nature. Biofilms were believed to protect constituent microorganisms from sanitizer treatment, provide a more suitable habitat for microorganisms, and become a site for genetic material exchanges between microorganisms. As we realize more about the significance of biofilm, methods used for biofilm study should be consistently developed and evaluated. To determine microbial attachment on surfaces, usually biofilms are grown on substratum surfaces and removed by vortexing with glass beads or scraping. However, scraping is not as effective as vortexing with glass beads. Another approach is direct-agar overlaying which cannot be used with high density biofilm. In this experiment, we compared effectiveness of glass beads (298±28 μm in diameter) and sands (width: 221±55 μm and length: 329±118 μm) in removing biofilm of Pseudomonas aeruginosa by vortexing method. The results suggested that acid-washed sands, which are significantly less inexpensive than glass beads, were as effective as (P>0.05) analytical grade glass beads in Pseudomonas aeruginosa biofilm removal without inhibiting growth of the organism.